Interview with Massimo Bianca and Massimo Franzoni. Discussions on the Civil Law - Feijoó Cambiaso, Raúl Humberto (2015)
In this interview, the outstanding Italian professors tell us their perspective on the main points of patrimonial civil law. In this way, the speakers explain matters related to the transfer of property system, breach of contract, tort, among others subjects; making brief comments, the authors also refer to the legislative options received in the Peruvian law.